Seroprevalence of coxiella Burnetii in Human and Animal Populations in Tiirkiye: Meta-Analysis - Kilbas, Imdat; Kahraman Kilbas, Elmas Pinar; Ciftci, Ihsan Hakki (Kafkas Univ, veteriner Fakultesi dergisi, 2023)
This study aims to reveal Coxiella burnetii by examining the studies reporting Q fever seroprevalence in humans and animals in the last 25 years in Turkiye. In this study, based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), various databases were searched between January 1997 and October. 2022. A literature review was carried out using data analyses performed using the IBM SPSS Version 25.0 statistical package program and Comprehensive Meta-Analysis (CMA) program. Overall prevalence of C. burnetii in humans was 22.78% (95% CI: 16.43%-29.12%), overall prevalence in animals was 13.49% (95% CI: 10.04-16.93%) was detected. The mean prevalence of C. burnetii in sheep was 19.1%+/- 10.88, 10.46 +/- 6.39% in cattle, 15.21 +/- 10.01% in studies including cattle and sheep together, 11.17 +/- 10.74 in cattle, sheep and goats, and 12.4%+/- 1.15% in sheep and goats. As a result of this study, it was determined that the prevalence of Q fever in humans in Turkiye is high in those dealing with animals, women who had a miscarriage, and infertile individuals. Although it is known that this disease is seen in Turkiye, there are not enough case reports in the literature. Detailed studies on Q fever in humans and animals need to be conducted. Further studies are needed to evaluate Q fever risk factors and prevalence data together within the scope of One Health approach.
CIFTCI, IHSAN HAKKI/0000-0002-9812-134X
Keywords: Cattle; Coxiella Burnetii; Infertility; Miscarry; Q Fever